Transgenerational effect in Taraxacum brevicorniculatum: test of a novel method of experimental plant DNA demethylation and its practical application in exploring the impact of maternal competition on progeny phenotype - Dvořáková, Hana (Jihočeská univerzita, 2017)
Spray application of 5azacytidine on established plant seedlings was tested for its demethylating efficiency, as it represents a novel method for plant experimental demethylation with a potentially lower negative impact on plant development compared to the traditional application of the demethytaling agent through germination of seeds in its solution. Further, the 5azacytidine spray application was used in practice to erase the epigenetic memory in offspring of Taraxacum brevicorniculatum plants from different competitive conditions. The impact of parental competition on the juvenile phenotype was estimated by measuring growth related traits, while the experimental demethylation allowed for evaluating the significance of DNA methylation marks in bioticaly induced transgenerational effects in T. brevirorniculatum.
Transgenerational effect in Taraxacum brevicorniculatum: test of a novel method of experimental plant DNA demethylation and its practical application in exploring the impact of maternal competition on progeny phenotype
Keywords: transgenerational effect; experimental DNA demethylation; 5-azacytidine; competition; seed mass; transgenerational effect; experimental DNA demethylation; 5-azacytidine; competition; seed mass